Business Philanthropy: Integrating Zakat and Sadaqah as Drivers of Business Growth at the Purwoharjo Branch of BMT NU East Java - Siti Nur Haliza; Imam Khusnudin (CV. Civiliza Publishing, 2026)
This study aims to analyze how the integration of zakat and sadaqah into business activities serves as a driving factor for business growth among members of BMT NU East Java, Purwoharjo Branch. The research employed a qualitative approach with a case study design to examine the practice of business philanthropy through the integration of zakat and sadaqah as catalysts for the growth of businesses operated by members of BMT NU East Java, Purwoharjo Branch. Data were collected through observation, in-depth interviews, and documentation involving eight purposively selected informants, consisting of BMT managers and entrepreneur members. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking to obtain credible and in-depth findings. The results indicate that the integration of zakat and sadaqah functions as a catalyst for business growth among BMT members through three main mechanisms. First, zakat and sadaqah foster a blessing-oriented business mindset that integrates economic, social, and spiritual objectives. Second, Islamic philanthropic practices enhance customer trust and loyalty by strengthening the business's image and moral legitimacy. Third, zakat and sadaqah expand social networks and business opportunities through the development of social capital that facilitates access to information and business collaboration. These findings demonstrate that Islamic philanthropy contributes to strengthening the resilience, competitiveness, and growth of micro-enterprises. Therefore, the development of Sharia-based MSMEs should integrate Islamic philanthropic values as the foundation of a sustainable and spiritually grounded business ecosystem.